Coarsening of metal/ceramics bicontinuous structures enhanced by stress-induced instability under cyclic thermal stress. (1st January 2023) - Abe, Ryota; Takahashi, Yuta; Watanabe, Yuta; Okuma, Gaku; Wakai, Fumihiro
Abstract: When a two-phase material has a bicontinuous and interpenetrating structure, the coarsening process during thermal annealing involves complex changes in morphology. Such a bicontinuous two-phase (solid/solid) structure is formed by sintering mixed metal and ceramic powders. This structure is used for electrodes in electronic devices. Here we demonstrate clearly that the coarsening of bicontinuous solid/solid two-phase material is accelerated by stress-induced instability similar to the ATG instability occurring in thin films. We used a metallic heating element embedded in a ceramic substrate as a model. The coarsening of Pt/alumina bicontinuous structure was enhanced by thermal stress during heating and cooling cycles. The coarsening was not appreciably affected by the electric current in Joule heating. The coarsening of the bicontinuous structure leads to the electrical breakdown of the electrodes. The analysis of stress-induced instability provides methods for improving the lifetime and reliability of electronic devices under thermal cycling. Graphical abstract: Image, graphical abstract